2008
DOI: 10.1007/s00280-007-0664-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetics of bevacizumab in patients with solid tumors

Abstract: The PK parameters were consistent with those of other IgG molecules. The results support dosing bevacizumab on a once every 2 weeks or once every 3 weeks dosing schedule on a mg/kg basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
213
3
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(257 citation statements)
references
References 12 publications
28
213
3
8
Order By: Relevance
“…The average half-life of serum proteins is about 1 day and even shorter for those that are freely filtered by the kidney. The half-life of aflibercept and bevacizumab, which are both molecules with Fc regions, is up to 3 weeks in systemic circulation (Lu et al 2008;Xu et al 2013). It has been established that the long persistence in systemic circulation of IgG and other Fc-conjugated proteins like aflibercept are due to their recycling and rescue from catabolic elimination by the FcRn via direct engagement of the Fc fragment (Roopenian & Akilesh 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The average half-life of serum proteins is about 1 day and even shorter for those that are freely filtered by the kidney. The half-life of aflibercept and bevacizumab, which are both molecules with Fc regions, is up to 3 weeks in systemic circulation (Lu et al 2008;Xu et al 2013). It has been established that the long persistence in systemic circulation of IgG and other Fc-conjugated proteins like aflibercept are due to their recycling and rescue from catabolic elimination by the FcRn via direct engagement of the Fc fragment (Roopenian & Akilesh 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A two-compartment model with first-order elimination estimated that the volume of distribution of bevacizumab was 2.39 l for a typical female and 3.29 l for a typical male, which is about the expected normal plasma volume [25]. Studies in Cynomolgus monkeys revealed that the weekly administration of 2-3 mg/kg bevacizumab resulted in sustained serum levels of 10 -30 g/ml, which appears to be enough to suppress VEGF activity.…”
Section: Distributionmentioning
confidence: 94%
“…Patients with low serum albumin (Ͻ29 g/l) have, on average, a 29% higher clearance rate, whereas patients with higher ALP (Ͼ483 IU/L) levels have a 23% higher clearance rate. Patients with elevated AST have an approximately 10% lower bevacizumab clearance rate [25]. The clearance of bevacizumab also depends on the tumor burden.…”
Section: Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 However, bevacizumab was found to have pharmacokinetic variability based on sex. 26 Although sex has not appeared to affect the efficacy of VEGF-targeted therapies, 25 further research should be performed to determine the true impact of sex on toxicity.…”
Section: -419-21mentioning
confidence: 99%